(untitled) (Communications in Mathematical Research, 2021)
In order to obtain much faster convergence, Müller introduced the left Gamma quasi-interpolants and obtained an approximation equivalence theorem in terms of ω^2r_φ(f, t)_p. Guo extended the Müller's results to ω^2r_φ^λ (f, t)_∞. In this paper we improve the previous results and give a weighted approximation equivalence theorem.